2015
DOI: 10.3390/chemosensors4010001
|View full text |Cite
|
Sign up to set email alerts
|

Building Selectivity for NO Sensing in a NOx Mixture with Sonochemically Prepared CuO Structures

Abstract: Several technologies are available for decreasing nitrogen oxide (NOx) emissions from combustion sources, including selective catalytic reduction methods. In this process, ammonia reacts with nitric oxide (NO) and nitrogen dioxide (NO 2 ). As the stoichiometry of the two reactions is different, electrochemical sensor systems that can distinguish between NO and NO 2 in a mixture of these two gases are of interest. Since NO and NO 2 can be brought to equilibrium, depending on the temperature and the surfaces tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, measurements were concluded only at one concentration (100 ppm) without any information concerning other conditions during the gas-sensing measurements, such as temperature and humidity. In [68], the authors developed a CuO-based gas sensor capable of selective detection…”
Section: Nitrogen Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, measurements were concluded only at one concentration (100 ppm) without any information concerning other conditions during the gas-sensing measurements, such as temperature and humidity. In [68], the authors developed a CuO-based gas sensor capable of selective detection…”
Section: Nitrogen Oxidesmentioning
confidence: 99%
“…However, measurements were concluded only at one concentration (100 ppm) without any information concerning other conditions during the gas-sensing measurements, such as temperature and humidity. In [68], the authors developed a CuO-based gas sensor capable of selective detection of NO in a NO x mixture in a dedicated environment, which was nitric oxide detection in combustion emissions. The gas-sensitive layer was deposited on an alumina substrate with IDEs (interdigitated gold electrodes) and thermally annealed at 320 or 500 • C. The developed sensors were tested in various conditions, close to the real conditions prevailing during the operation of internal combustion engines, e.g., 300 ppm NO with increasing concentrations of NO 2 : 68 ppm, 113 ppm, 180 ppm, and 225 ppm.…”
Section: Nitrogen Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…12−15 To date, many onboard sensing studies have been conducted to detect NO and NO 2 separately. 16 However, much fewer studies have been reported on the measurement and analysis of a mixture of NO and NO 2 . Most studies focus on evaluating the selectivity against interfering analytes with both in their pristine form or with a negligible response of interfering gas.…”
mentioning
confidence: 99%
“…In the current sensor development, onboard and real-time measurement of the gaseous mixture has been proven extremely challenging due to low selectivity and response to various gases and severe cross-sensitivity. , Owing to their small size and good energy efficiency, solid-state sensors based on chemiresistors are ideal for in situ and real-time gas monitoring, whereas the transducing signal could be transmitted via a wireless system. To date, many onboard sensing studies have been conducted to detect NO and NO 2 separately . However, much fewer studies have been reported on the measurement and analysis of a mixture of NO and NO 2 .…”
mentioning
confidence: 99%